Actualización de la plataforma estratégica (misión y visión) de la E.S.E Hospital San José de San Bernardo del Viento en Córdoba (2022)
The ESE HOSPITAL SAN JOSE is a first level of complexity Health Provider Institution that, according to the provisions of the National Social Security System, has as its characteristics the focus on the provision of health services and the promotion and prevention in Health. The objective of this research was to update the strategic platform taking into account the conceptualization of mission and vision in a health institution. Once the information is collected, we will focus on creating a DOFA matrix, which will serve as the basis for focusing on the mission and vision of the strategic plan. As a final phase, the creation of a strategy will be carried out that allows potentiating the activities that are executed in Hospital. Taking into account the above, the ESE HOSPITAL SAN JOSE, belonging to the municipality of San Bernardo del Viento - Córdoba, part of the strengthening of its strategic platform, which must be updated and make its information visible to the community, designing strategies that allow adequate development of their commitment.